Sistem Kendali Fuzzy Bertipe-2 Interval dengan Struktur Adaptif Beracuan Model - Bambang Riyanto; Wakhyu Dwiono (Institute for Research and Community Services (LPPM) ITB, 2006)
Adaptive fuzzy controller is a fuzzy controller that has ability to change its parameters when the plant's operating conditions vary. In this paper, design and implementation of model reference adaptive fuzzy control are presented. Interval type-2 fuzzy logic controller with PD-like action is employed and its performance is studied. The fuzzy controller structure is applied to control an inverted pendulum. Simulation and experimental study shows that by using similar membership function, fuzzy rules and scaling, interval type-2 adaptive fuzzy logic controller provides better control system performance compared to type-1 fuzzy controller.